Automated mold manufacturing system design - Tan, Gen Ming (2008)
It is the intention of this project, to turn mold making into a production-oriented process and to change the driving force from Moldmaker-driven to Engineering-driven manufacturing. The flexible automation system offers a closed manufacturing loop that provides integration among robots, machines and inspection equipment. This project designs an automated mold manufacturing system, consisting of a master robot for the delivery of workpieces to machinery or other equipment under the control of WSM. The dissertation also discusses an effective management system (MAPAZ system) for an integrated information flow and manufacturing administration in the mold manufacturing.